Pengembangan Media Pembelajaran Technical English Berbasis Digital - Dharmawati Dharmawati, Sumi Khairani, Diana Suita (Query: Journal of Information Systems, 2017)
This research is conducted based on the problem in teaching learning process of technical English for civil engineering in STT Harapan Medan. The use of lecturer method, copied and printed teaching material make the students unmotivated to learn English. The solution for this problem, it is needed to develop learning media based on CAI  (Computer Aided Instruction). The objective of this research is developing digital English media designed for civil engineering students. This research conducted qualitative method using Development Research methodology, it is used Four D Model.  Case of this research in STT Harapan Medan. The result of this research is the application of digital teaching materials in learning technical English, especially in grammar in civil engineering class. The digital teaching materials for grammar was designed by using SOM application and the exercise was designed by using cartoon story maker. Keywords:  Computer Aided Instruction, Multimedia